Are Carbon Nanotubes a Naturally Occurring Material? Hints from Methane CVD Using Lava as a Catalyst - Mracek, J; Fagan, R; Stengelin, R; Hesjedal, T (2011)
Single-walled carbon nanotubes (SWNTs) were grown using methane CVD with lava as a catalyst and substrate. Metal-oxide phases embedded in the lava are reduced in the presence of hydrogen, thereby promoting catalytic growth. Scanning electron microscopy and energy-dispersive X-ray spectroscopy show a correlation between the growth of carbonaceous nanomaterials and the presence of iron in the alumina matrix. Raman spectroscopy of the carbon deposits proves the occurrence of SWNTs. Although this growth route lacks ef-ficiency, it provides evidence for the claim that SWNTs are a natural allotrope of carbon and that volcanoes may provide an environment for their synthesis. © 2011 Bentham Science Publishers Ltd.